1986
DOI: 10.1111/j.1530-0277.1986.tb05112.x
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary‐Adrenal Responses to Morphine and Footshock Stress Are Enhanced following Prenatal Alcohol Exposure

Abstract: The effect of prenatal ethanol exposure on pituitary-adrenal function in adult offspring was assessed by measuring corticosterone (CS) levels in plasma following exposure to two forms of footshock stress, intermittent and continuous, and after administration of 20 mg/kg of morphine. The footshock experiments were conducted at two time points in the circadian pituitary-adrenal cycle. Prenatally ethanol-exposed (E) rats had higher levels of CS than pair-fed and normal controls following intermittent footshock wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1
2

Year Published

1988
1988
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(43 citation statements)
references
References 26 publications
4
36
1
2
Order By: Relevance
“…Previous studies have indicated that adult females are more susceptible than males to some of the effects of prenatal alcohol (29,33,58,59,64). Our study appears to follow the same sexually dimorphic pattern.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies have indicated that adult females are more susceptible than males to some of the effects of prenatal alcohol (29,33,58,59,64). Our study appears to follow the same sexually dimorphic pattern.…”
Section: Discussionsupporting
confidence: 67%
“…Also, "anger-prone" 15 month-old infants exhibit augmented CORT response when confronted with a stranger or a frightening robot-toy (48). In rodents, FAexposure leads to either LHPA axis hyper-responsiveness to stressors or delayed or deficient return to pre-stress level (49,50,51,52,53,54,55,56). In this study, the effects of FA-exposure on increased infant irritability and LHPA axis responsiveness were most prominent in rhesus monkeys carrying the s allele.…”
Section: Discussionmentioning
confidence: 58%
“…First, FAE offspring are known to be stress-hyper-responsive. 47,48 Hence, a visual platform test at the beginning of the training could affect the results of the spatial learning task differentially. Presenting the visual platform at the end of the training would not differentiate the learning impairment from the visual impairment.…”
Section: Forced Swim Testmentioning
confidence: 99%